1991
DOI: 10.1093/ajcp/96.4.529
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen and Progesterone Receptors in Lymphangioleiomyomatosis, Epithelioid Hemangioendothelioma, and Sclerosing Hemangioma of the Lung

Abstract: The therapeutic options in the treatment of lung neoplasia usually have not included hormonal therapy, unlike those for primary tumors of other sites (e.g., breast). However, two mesenchymal proliferations of lung, lymphangioleiomyomatosis and epithelioid hemangioendothelioma (EHE), and one epithelial tumor, sclerosing hemangioma (SH), have a significant female predilection and may benefit from such hormonal therapy. The authors investigated five cases each of EHE and lymphangioleiomyomatosis and four cases of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(27 citation statements)
references
References 0 publications
0
27
0
Order By: Relevance
“…[9][10][11] Even though many studies have been published to date, the effective treatment mode for lymphangioleiomyomatosis is still obscure. But considering the fact that lymphangioleiomyomatosis usually develops in females of reproductive age, 1,2 and that cells of lymphangioleiomyomatosis contain receptors for estrogen and progesterone, 12 that pregnancy and estrogen administration aggravates lymphangioleiomyomatosis, 13,14 the etiology of this disease is closely related to hormones. The current treatment modality for lymphangioleiomyomatosis is primarily based on the antagonism of estrogen action, and are empiric and unproven.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11] Even though many studies have been published to date, the effective treatment mode for lymphangioleiomyomatosis is still obscure. But considering the fact that lymphangioleiomyomatosis usually develops in females of reproductive age, 1,2 and that cells of lymphangioleiomyomatosis contain receptors for estrogen and progesterone, 12 that pregnancy and estrogen administration aggravates lymphangioleiomyomatosis, 13,14 the etiology of this disease is closely related to hormones. The current treatment modality for lymphangioleiomyomatosis is primarily based on the antagonism of estrogen action, and are empiric and unproven.…”
Section: Discussionmentioning
confidence: 99%
“…15 Recently, the use of oral progestins or GnRH-a (Gonadotropin releasing hormone agonists) has also been reported in case studies and small series. 12,16,17 Despite a wide variety of treatment modes that have been introduced since the first description of lymphangioleiomyomatosis, patient survival has not improved appreciably. Because of the slow progression of the disease, a report has shown that mortality can within 10 years after diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Standard recombinant DNA technologies were utilized to develop mammalian expression constructs of TSC2 as previously described (20,24,26). The GST fusion constructs of TSC2 are described elsewhere (26).…”
Section: Plasmid Constructsmentioning
confidence: 99%
“…Aberrant expression of TSC2 (tuberin) occurs in the lungs and kidneys of patients with lymphangioleiomyomatosis, a disease that primarily affects females (19 -21). Furthermore, loss of function of TSC2 is associated with aberrant ER expression in proliferating smooth muscle cells found in the kidney and lung, suggesting that tuberin is involved in regulating the response of smooth muscle cells to estrogen (20,22,23). Although tuberin has not been shown to have direct transcriptional capacity, it has been shown that overexpression of tuberin in HEK 293 cells inhibits steroid-and ER-mediated transcription (24 -26).…”
mentioning
confidence: 99%
“…1 These clinical observations were initially substantiated by early experiments in the 1980s using radioligand assays, which confirmed the presence of the estrogen receptor (ER) in vascular tumors; 2,3 however, with the advent of immunohistochemical techniques, subsequent studies performed in the 1990s with antibodies raised against the ER refuted these earlier data and it appeared that the newer technology had exposed the limitations of the older biochemical assays. [4][5][6][7] Recently, an additional ER subtype, estrogen receptor beta (ERb), 8 was identified and the previous ER against which the original antibodies were raised was renamed estrogen receptor alpha (ERa). Although ERa has been assessed immunohistochemically in vascular neoplasms and found to be absent, ERb has not been previously characterized in these entities.…”
mentioning
confidence: 99%